Effect of Harvest Period on the Proximate Composition and Functional and Sensory Properties of Gari Produced from Local and Improved Cassava (Manihot esculenta) Varieties - Alphonse Laya; Benoît Bargui Koubala; Habiba Kouninki; Elias Nchiwan Nukenine (International Journal of Food Science)
This study is aimed at evaluating the proximate composition and functional and sensory characteristics of gari obtained from five cassava varieties (EN, AD, TMS92/0326, TMS96/1414, and IRAD4115). These cassavas were harvested during the dry season 12 months after planting (12MAP) and in the rainy season (15MAP). Results showed that the characteristics of gari varied significantly (p<0.05) with the variety and the harvest period. Gari from EN cassava harvested at 12MAP had the highest total carbohydrates (78.07% dry weight), starch (61%), and proteins content, while gari from TMS 96/1414 variety (12MAP) had high amino acids (10.25 mg/g) and phenolic compounds (9.31 mg/g) content. The gari from IRAD4115 had the highest value of ash content (20.62 mg/g) at 12MAP. The soluble sugar content was high in the gari from cassava harvested at 12MAP while free cyanide reduced significantly in gari from cassava harvested at 12MAP. The water absorption capacity, swelling power, and bulk density were significantly (p<0.05) high in the gari from EN cassava variety at 12MAP. Compared to commercial gari (3.30), gari from EN local cassava had the best overall acceptability (4.35) followed by those obtained from TMS92/0326 and TMS92/1414 varieties, respectively.